The structure of posttraumatic stress symptoms in survivors of war : A confirmatory factor analysis of the Impact of Event Scale—Revised - Morina, Nexmedin (Array, 2010)
Objective: The study aimed at establishing the factor structure of the Impact of Event Scale-Revised (IES-R) in survivors of war. Methods: A total sample of 4.167 participants with post-traumatic stress symptoms following the war in Ex-Yugoslavia were split into three samples: Two independent samples of people who stayed in the area of conflict and one sample of refugees to Western European countries. Alternative models with 3, 4, and 5 factors of posttraumatic symptoms were tested in one sample. The findings were cross-validated in the other two samples. Results: The model of best fit had 5 factors, i.e. intrusion, avoidance, hyperarousal, numbing, and sleep disturbance. Model superiority was cross-validated in two other samples. Conclusions: These findings suggest a 5 factor model of posttraumatic stress symptoms in war survivors with numbing and sleep disturbance as separate factors in addition to intrusion, avoidance and hyperarousal.